Genome-Wide Association Study Reveals Multiple Loci Associated with Primary Tooth Development during Infancy ... : تكشف دراسة الجمعية على مستوى الجينوم عن مواقع متعددة مرتبطة بتطور الأسنان الأولية أثناء الطفولة ... - Demetris Pillas; Clive Hoggart; David M. Evans; Paul F. O'Reilly; Kirsi Sipilä; Raija Lähdesmäki; Iona Y. Millwood; Marika Kaakinen; Gopalakrishnan Netuveli; David Blane; Pimphen Charoen; Ulla Sovio; et al. (OpenAlex, 2010)
Tooth development is a highly heritable process which relates to other growth and developmental processes, and which interacts with the development of the entire craniofacial complex. Abnormalities of tooth development are common, with tooth agenesis being the most common developmental anomaly in humans. We performed a genome-wide association study of time to first tooth eruption and number of teeth at one year in 4,564 individuals from the 1966 Northern Finland Birth Cohort (NFBC1966) and 1,518 individuals from the Avon Longitudinal Study of Parents and Children (ALSPAC). We identified 5 loci at P<5x10(-8), and 5 with suggestive association (P<5x10(-6)). The loci included several genes with links to tooth and other organ development (KCNJ2, EDA, HOXB2, RAD51L1, IGF2BP1, HMGA2, MSRB3). Genes at four of the identified loci are implicated in the development of cancer. A variant within the HOXB gene cluster associated with occlusion defects requiring orthodontic treatment by age 31 years. ... : نمو الأسنان هو عملية وراثية للغاية تتعلق بعمليات النمو والتطور الأخرى، والتي تتفاعل مع تطور المجمع القحفي الوجهي بأكمله. تشوهات نمو الأسنان شائعة، مع كون تكاثر الأسنان هو الشذوذ التنموي الأكثر شيوعًا لدى البشر. أجرينا دراسة ارتباط على مستوى الجينوم للوقت لأول ظهور للأسنان وعدد الأسنان في عام واحد في 4564 فردًا من مجموعة الولادة في شمال فنلندا لعام 1966 (NFBC1966) و 1518 فردًا من دراسة أفون الطولية للوالدين والأطفال (ALSPAC). حددنا 5 مواضع في P<5x10(-8)، و 5 مع ارتباط إيحائي (P< 5x10 (-6)). تضمنت المواضع العديد من الجينات المرتبطة بتطور الأسنان والأعضاء الأخرى (KCNJ2، EDA، HOXB2، RAD51L1، IGF2BP1، HMGA2، MSRB3). الجينات في أربعة من المواضع المحددة متورطة في تطور السرطان. متغير داخل مجموعة الجينات HOXB المرتبطة بعيوب الإطباق التي تتطلب علاجًا لتقويم الأسنان بحلول سن 31 عامًا. ...